The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/j.pain.0000000000002127
|View full text |Cite
|
Sign up to set email alerts
|

Cage-lid hanging behavior as a translationally relevant measure of pain in mice

Abstract: Supplemental Digital Content is Available in the Text. Cage-lid hanging behavior is impaired by sustained pain in mice and can be used as an ethologically valid and translationally relevant pain outcome measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…37 Motor behavior is the most commonly used method to assess the degree of pain in animal models. 42 Zhang et al 31 We used MRI to assess the characteristics of IDD in cynomolgus monkeys. The study found that with increasing age, the IVDs in cynomolgus monkeys underwent degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…37 Motor behavior is the most commonly used method to assess the degree of pain in animal models. 42 Zhang et al 31 We used MRI to assess the characteristics of IDD in cynomolgus monkeys. The study found that with increasing age, the IVDs in cynomolgus monkeys underwent degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have characterized a variety of spontaneous mouse behaviors that may be reflective of pain state, including free-choice temperature preference assays. 10 , 11 , 13 , 16 19 , 38 However, most assays used to assess thermal preference rely on mouse avoidance responses to noxious temperatures rather than assessment of native preference. 11 In contrast, our assay does not necessarily expose mice to noxious temperature ranges and therefore provides a measure of response to innocuous temperature, allowing for a study of thermal allodynia or thermotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work done in our lab has shown that gabapentin at 100 mg/kg produces analgesia without impacting locomotion in mice. 38 After another 30 minutes, they were recorded in the arena for 30 minutes. All capsaicin injections were conducted after placing the mice under light isoflurane anesthesia, with toe-pinch reflex present.…”
Section: Methodsmentioning
confidence: 99%
“…The assays performed in the preclinical portion of this study were all conducted in a testing room and examined pain behaviors in various contexts such as evoked pain, spontaneous pain, and muscle strength. We acknowledge that animal behavior in this context may not completely reflect home-cage behavior, such as voluntary wheel-running, cage-lid hanging, and general home-cage activity, which reduces stress from test that occur out of the animal's home environment (60,61). Home-cage behaviors may also be more translational to quality-of-life assessments.…”
Section: Discussion: (1496 Words)mentioning
confidence: 99%